The Moderating Role of Profitability: Market Value Edge, Debt-to-Equity Ratio, Earnings Per Share, and Financial Leverage on Stock Prices - Hukum, Nur’Amria A R Hukum; Ali, Iqbal Muhammad Aris; Sinen, Kasim (Atestasi : Jurnal Ilmiah Akuntansi, 2025)
Purpose: This study investigates the influence of Market Value Added, Debt to Equity Ratio, Earnings Per Share, and Financial Leverage on stock prices, considering Profitability as a moderating factor in technology firms listed on the Indonesia Stock Exchange from 2018 to 2022. Research Design and Methodology: A quantitative approach, utilizing purposive sampling, yielded 52 observations from unbalanced panel data. Variables were analyzed using panel data regression and Moderated Regression Analysis (MRA) in Eviews 12.0 to examine the relationships among financial indicators and stock valuation. Findings and Discussion: The analysis reveals that Market Value Added, Debt-to-Equity Ratio, and Earnings Per Share do not have a significant impact on stock prices. In contrast, Financial Leverage has a positive influence. Profitability moderates the relationship between Market Value Added and stock prices negatively, while no moderating effect is observed for the other variables. Implications: The findings highlight the limited predictive power of certain financial ratios within the technology sector and the conditional role of Profitability. Future inquiries should include broader indicators or sector-specific dynamics to enhance understanding and guide investment or policy decisions.